Association Between Stunting and Anemia Among Toddlers: Stratified by Characteristic of Family and Immunization Status in Mlonggo District, Jepara Regency - Arwinda Nugraheni; Muflihatul Muniroh; Yora Nindita; Firdaus Wahyudi; Bambang Hariyana (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: The risk of anemia in stunted toddlers is higher than in normal toddlers. There is limited research on anemia in children under 3 years old in the community and there is a need for supporting research to prove the possibility of controlling stunting and anemia together. Previous studies have shown that family characteristics and immunization status are associated with the stunting and anemia.Objective: This study aims to analyze the association between anemia and stunting in toddlers that are stratified by characteristics of family and Immunization status.Methods: This study used a cross-sectional design study and was conducted on September-October 2020 in the Mlonggo District, Jepara Regency. One hundred two respondents were selected by cluster random sampling technique. The questionnaire was applied to collect the data on stunting, anemia, immunization status, age, mother's occupation and education status, SCREEM score, and APGAR score. This study used the Chi-Square statistic test.Results: The anemia status was measured by the Hb meter. The characteristics of stunting status (stunting = 17.7%, no stunting= 82.3%), anemia status (Yes = 63.7%, No = 36.3%). The association between stunting and anemia was stratified by the child age (6-23 months) (PR=1.667; 95%; CI=1.103-2.519; P=0.123), employed mother (PR=1.593; 95%CI=1.265-2.005; P=0.154), incomplete and inappropriate immunization status (PR=1.636; 95%CI= 1.132-2.366; P=0.133) and highly internal family function; (PR=1.512; 95% CI=1.270-1.799; P=0.029).Conclusion: There was an association between stunting and anemia in toddlers from child age of 6-23 months, employed mother, incomplete and inappropriate immunization, and highly family function groups.